Teachers’ aggressive and violent behaviours towards students with mild intellectual disabilities in three forms of education - Buchnat, Marzena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Aggression and violence has become a regular part of school reality. The ongoing legal changes in the education system have provided children with mild intellectual disabilities the opportunity to study in three forms of education: mainstream schools, integration classes and special schools. Unfortunately, the results of many studies have revealed that students with disabilities are more likely to be subject to peer victimization, particularly in various forms of inclusive education. In view of such facts, the question arises whether, and if so, how and with what frequency students with mild intellectual disabilities in various forms of education experience aggression and violence perpetrated by teachers. This seems particularly important because of the role that teachers play in building a sense of security in students, especially those with mild intellectual disabilities. The results of the study revealed a much higher level of aggression and violence experienced by students with mild intellectual disabilities perpetrated by teachers working in mainstream schools compared to those working in special schools. This fact raises great reservations regarding the teachers’ attitude towards students with mild intellectual disabilities and the level of their preparation for effective work with such students.